Computers and employment: The truth about e-skills - Luc Soete; Bas ter Weel (EIB Papers, 2001)
When compared to other technological breakthroughs, information and communication technologies (ICT) appear to have at least two unique features. One is the long, unremitting technological improvement that has taken place in these technologies during the post-war period. A second unique feature is the exceptional technological spillovers that are possible throughout the economy. This paper addresses the particular question of the impact of this 'new' digital environment on the labour market. It will investigate in particular how ICT has changed and is changing the labour market and the 'old', classical insights into the relationship between technology, employment and skills. We start in Section 2 with a review of the literature on technology and employment. In previous centuries, but also in recent decades, new technologies were often identified with employment 'destruction'. They were feared to be one of the main causes of unemployment amongst unskilled workers and at the origin of most of the new, so-called 'biased' opportunities in favour for more skilled workers. Ever since the so-called Luddites smashed the power looms and spinning jennies that threatened their livelihood in the early 19th century, the popular fear that technological change would increase unemployment has existed and continued even in boom years.
Keywords: 330; Informationstechnik; Beschäftigungseffekt; Humankapital; OECD-Staaten